(untitled) (Fiep Bulletin - online, 2013)
Social inclusion can be defined as a process in which companies and people with disabilities seeking adapt to one another, to the assimilation of opportunities and therefore, a society for all (Sassaki, 1997). Physical activity for the disabled person provides rehabilitation and fitness, but mainly provides the integration and enhancement of those people in society. People with disabilities feel more accepted, improve their self-esteem and their quality of life, demystify the image of useless and property of the person with disabilities (Luz, 2003). This study is to propose a reflection of educators and researchers on the social inclusion of persons with disabilities, and discuss the responsibility of Physical Education in the search for effective interventional procedures, through analysis of the literary review.